2014
DOI: 10.4081/idr.2014.5327
|View full text |Cite
|
Sign up to set email alerts
|

A complicated case of an immunocompetent patient with disseminated nocardiosis

Abstract: Nocardia species are aerobic, gram positive filamentous branching bacteria that have the potential to cause localized or disseminated infection. Nocardiosis is a rare disease that usually affects immunocompromised patients and presents as either pulmonary, cutaneous or disseminated nocardiosis. Forty-two year-old hispanic male presented to our care with bilateral lower extremity weakness, frontal headache, subjective fever, nausea, and vomiting. Brain computed tomography (CT) revealed multiple hyperdense lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 24 publications
0
23
0
2
Order By: Relevance
“…is opportunistic pathogens of immune compromised patients [9,10]. No source of infection could be detected in the current case as Nocardia are found in environment worldwide in fresh and salt water and soil type, dusts and fecal deposit of animal [11].…”
Section: Discussionmentioning
confidence: 74%
“…is opportunistic pathogens of immune compromised patients [9,10]. No source of infection could be detected in the current case as Nocardia are found in environment worldwide in fresh and salt water and soil type, dusts and fecal deposit of animal [11].…”
Section: Discussionmentioning
confidence: 74%
“…Gram stain showing filamentous branched gram positive bacilli is the most sensitive method for diagnosis. Further it can be seen as acid fast structures in MAFS [3] .…”
Section: Disussionmentioning
confidence: 99%
“…No randomized trials have been performed to determine the most effective antibiotic regimen for nocardiosis. However, trimethoprim-sulfamethoxazole is considered the mainstay of therapy since most studies have shown a favorable susceptibility to this antibiotic [3] . CNS nocardiosis usually results after pulmonary nocardiosis but pulmonary infection or other focus of infection could not be substantiated in this patient at the time of admission.…”
Section: Disussionmentioning
confidence: 99%
See 2 more Smart Citations